A Cost-Effective and Efficient DC Converter Driver Circuit for Photovoltaic Applications using Timer 555 Control Circuit - Lawrence Sii, Ying Ting; Yi Lung, Then; Hazrul, Mohamad Basri; Abadi, Chanik; Maxentia Chiet, Chiet Ong; Hadi Nabipour, Afrouzi (Semarak Ilmu Sdn Bhd, 2025)
This paper presents a cost-effective and efficient DC converter driver circuit designed for photovoltaic (PV) applications. The circuit utilizes the Timer 555 as the control circuit for regulating the input voltage of the DC-DC boost converter. Simulation results obtained using Multisim software demonstrate the feasibility and effectiveness of the proposed circuit. The simulation results reveal that the circuit successfully increases voltages and decreases currents as load resistance rises, while significantly reducing load power with higher load resistance. Furthermore, the simulated boost converter achieves a higher output voltage and demonstrates an efficiency range of 91.42% to 92.54%, indicating its ability to efficiently convert input power into desired output power. These findings highlight the promising performance of the designed circuit for PV applications, offering effective power conversion and acceptable load current.